EXOGENOUS DRIVERS Of SURfACE URBAN HEAT ISLANDS IN NORTHERN wEST SIBERIA - I. Esau; V. Miles (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2018)
Urban temperature anomalies, frequently referred to as the urban heat islands (UHIs), are of the most distinct and influential climatic factors with significant impact on urban life and environment. However, UHIs in high latitudes are still studied only fragmentary. There is a knowledge gap related to the urban temperature distinction with respect to local temperature anomalies of natural surface types. This study extends upon our recent high latitude regional-scale climatic survey in 28 cities in the Northern West Siberia (NWS) region. Based on MODIS land surface temperature (LST) products covering 15 years between 2001 and 2015, it was revealed that all 28 cities have significant surface urban heat islands (SUHIs). The strong statistical dependence (r = 0.73) on endogenous factors such as city size and the population was found. It was suggested that exogenous factors such as the background LC types could be significant as well. This study presents the analysis of the exogenous factors shaping the apparent SUHI intensities. The major contribution to the SUHI was revealed for water, sparse vegetation, grassland, and shrubland. There are no clear dependence between the partial SUHI intensity and the area fraction occupied by the given LC type. The mechanisms and pathways of the SUHI maintenance cannot be inferred solely from the remote sensing data. Further understanding requires numerical experiments with turbulence-resolving models.